2017
DOI: 10.1093/eurheartj/ehx458
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of three-vessel fractional flow reserve measurement in patients with coronary artery disease

Abstract: 3V FFR-FRIENDS study (https://clinicaltrials.gov/ct2/show/NCT01621438, NCT01621438).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 22 publications
3
46
0
Order By: Relevance
“…The study population was derived from the 3V FFR-FRIENDS study (3-vessel FFR for the assessment of total stenosis burden and its clinical impact in patients with coronary artery disease, NCT01621438) 16 and the 13 N-ammonia PET registry. 10,17, 18 In both studies, patients with depressed left ventricular systolic function (ejection fraction <35%), acute ST-elevation myocardial infarction (MI) within 72 h, previous coronary artery bypass graft surgery (CABG), chronic renal disease, abnormal epicardial coronary flow (TIMI flow <3) or planned CABG after diagnostic angiography were excluded.…”
Section: Study Design and Patient Populationmentioning
confidence: 99%
“…The study population was derived from the 3V FFR-FRIENDS study (3-vessel FFR for the assessment of total stenosis burden and its clinical impact in patients with coronary artery disease, NCT01621438) 16 and the 13 N-ammonia PET registry. 10,17, 18 In both studies, patients with depressed left ventricular systolic function (ejection fraction <35%), acute ST-elevation myocardial infarction (MI) within 72 h, previous coronary artery bypass graft surgery (CABG), chronic renal disease, abnormal epicardial coronary flow (TIMI flow <3) or planned CABG after diagnostic angiography were excluded.…”
Section: Study Design and Patient Populationmentioning
confidence: 99%
“…7 A substudy conducted in over 435 patients suggested that RFR and IFR have same diagnostic accuracy in predicting cardiovascular outcomes. 8 Recent study done in acute myocardial infarction patients comparing RFR with FFR observed that correlation between RFR and FFR was 0.84, overall agreement was 82%. 9 Studies comparing FFR and RFR are still lacking, so we conducted a study on 33 patients who were undergoing physiological assessment FFR to identify the significance of lesion; RFR values were also taken.…”
Section: Discussionmentioning
confidence: 95%
“…This could be either in the form of decisionmaking strategy trials like RIPCORD, or in-country large registries like SCAAR (Sweden). Several groups of APAC countries recently published the results of important physiologic studies and those study results from APAC need to be highlighted [19,26,[45][46][47][48][49][50]. The group also felt that in-country registry data can provide good scientific evidence to respective health authorities to incorporate invasive physiology in guidelines and reimbursement.…”
Section: Evidencementioning
confidence: 99%